1986
DOI: 10.1161/01.atv.6.5.465
|View full text |Cite
|
Sign up to set email alerts
|

Peanut oil reduces diet-induced atherosclerosis in cynomolgus monkeys.

Abstract: The atherogenicity of dietary peanut oil (PO) was examined in cynomolgus monkeys fed semipurified diets for 15 months. Four groups of six monkeys were fed diets containing 0.22 mg/kcal (0.1%) cholesterol and 0%, 5%, 10%, or 20% PO. An additional group was fed 2.0% cholesterol and 20% PO to serve as a literature control. Increasing the concentration of PO in the diet was associated with significant decreases in total plasma cholesterol (p < 0.05) and the total/HDL cholesterol ratio (p < 0.05) and an increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Although one study showed that peanut oil was atherogenic when fed to rats and rabbits,21 in another study it was antiatherogenic when fed to cynomolgus monkeys; the blend of fats approximated the fatty acid composition of the average diet in the United States 2223…”
Section: Discussionmentioning
confidence: 99%
“…Although one study showed that peanut oil was atherogenic when fed to rats and rabbits,21 in another study it was antiatherogenic when fed to cynomolgus monkeys; the blend of fats approximated the fatty acid composition of the average diet in the United States 2223…”
Section: Discussionmentioning
confidence: 99%
“…This protective finding for a MUFA-enriched diet is not supported by one study in monkeys [7], a study in LDL receptor-null, human apolipoproteinB-overexpressing transgenic mice [43] and one study in LDL receptor-deficient mice [44]. On the other hand, the antiatherosclerotic properties of MUFA-enriched diets have been demonstrated in rabbits [45][46][47][48] and monkeys [49,50], our own previous studies in hamsters [13], and in swine [51,52]. There are several possible mechanisms derived from both in vitro and in vivo studies that might explain the beneficial effects of MUFA-containing diets as they relate to early atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%